Implementation of Spiritual Therapy for Mental Disorders in Purbalingga Indonesia Mental Rehabilitation Centers - Wahyuningsih, Dyah; Riyadi, Sugeng (International Journal of Scientific Research and Management (IJSRM), 2024)
In the era of materialism, the pressures and demands in life increase various kinds of physical and psychological suffering. Mental disorders are a phenomenon that is increasing from year to year. This study describes the practice of applying spiritual therapy for mental disorders in rehabilitation homes. This research uses a qualitative approach with a case study method. The research subjects were one assistant therapist, two rehabilitation center administrators, and two patients with mental disorders. The results showed that a Kyai carried out spiritual therapy with prayer therapy methods, dhikr, rukyah syar'iyah, and drinking karomah water. Spiritual therapy is proven to heal patients and make them more independent and able to socialize with the environment.